Literarische finnisch-deutsche Beziehungen bis 1918 - Mrozewicz, Bolesław (Folia Scandinavica Posnaniensia, 2009)
The article ‘Literary Finnish-German relations until 1918’ broaches less known and less frequently analysed aspects of literary and cultural contacts between Finland and Germany. First of all, the author brings into focus the development of the Finnish literary production in the 16th century. It took place in close connection with the Reformation, which reached Finland from Germany (especially Wittenberg) via Sweden. As a centre of learning, Germany drew most of the Finnish students who were to play a major role in the religious and cultural life of Finland. Among other were the Reformer Peder Särkilax and the bishop M. Agricola, the author of the first ABC-book in Finnish and the translator of the New testament. Second, the article emphasises that until the 19th century, it were the Fins who were influenced by the German literary achievements. After the publication of the Finnish literary epic ‘Kalevala’ in 1835–49, the direction of literary impulses changed. The articles and lectures of Jacob Grimm on Finnish literature (1845) generated avid interest in Germany, a tendency which has lived on ever since.